2016
DOI: 10.1590/1676-0611-bn-2016-0218
|View full text |Cite
|
Sign up to set email alerts
|

New isolates of Trichoderma antagonistic to Sclerotinia sclerotiorum

Abstract: Forty-nine isolates of Trichoderma from the Brazilian Midwest were evaluated for their antagonistic activity in vitro against Sclerotinia sclerotiorum (causal agent of white mold), which were then identified based on their nuclear ribosomal ITS sequences. Paired culture tests showed that all isolates exhibited some antagonism, with a maximum of 77% mycelial inhibition and complete inhibition of sclerotia production. Two isolates were found to be the most promising biocontrol agents, considering both antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Ahmed (2016) recorded that under greenhouse conditions, treated bean seeds with B. subtilis and T. harzianum significantly reduced the incidence of Rhizoctonia solani damping-off, as well as caused a considerable increase in the activity of peroxidase and polyphenoloxidase enzymes. Marques et al (2016) showed that Trichoderma koningiopsis and T. brevicompactum isolates with good antagonistic potential for S. sclerotiorum were considered to be promising for both biocontrol parameters (inhibition of mycelial growth and reduction of sclerotia). Zhang et al (2016) found that T. harzianum increased resistance against S. sclerotiorum infection in soybean seedlings, also, primed pathogenesis-related proteins expression after S. sclerotiorum challenge, increased the activity of the antioxidant enzymes peroxidase PO, superoxide dismutase SOD, and catalase CAT and, improved the contents of chlorophyll and phenolic, indicating that these physiological and molecular mechanisms are involved in the induction of systemic resistance by T. harzianum.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed (2016) recorded that under greenhouse conditions, treated bean seeds with B. subtilis and T. harzianum significantly reduced the incidence of Rhizoctonia solani damping-off, as well as caused a considerable increase in the activity of peroxidase and polyphenoloxidase enzymes. Marques et al (2016) showed that Trichoderma koningiopsis and T. brevicompactum isolates with good antagonistic potential for S. sclerotiorum were considered to be promising for both biocontrol parameters (inhibition of mycelial growth and reduction of sclerotia). Zhang et al (2016) found that T. harzianum increased resistance against S. sclerotiorum infection in soybean seedlings, also, primed pathogenesis-related proteins expression after S. sclerotiorum challenge, increased the activity of the antioxidant enzymes peroxidase PO, superoxide dismutase SOD, and catalase CAT and, improved the contents of chlorophyll and phenolic, indicating that these physiological and molecular mechanisms are involved in the induction of systemic resistance by T. harzianum.…”
Section: Discussionmentioning
confidence: 99%
“…Since all isolates produced active NVMs against S. sclerotiorum, the results were compared with those obtained in previously performed dual culture tests (Marques et al 2016), and a greater inhibition was observed with the use of the culture filtrates than in the direct comparison between pathogen and antagonist. This fact suggests that the main mechanism of action of these isolates is antibiosis, that is, the production of secondary compounds with antibiotic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Research Corporate), already characterized and identified in previous studies (Marques et al 2016), were used. According to the study cited, these isolates exhibited antifungal activity in dual culture tests in vitro against S. sclerotiorum, and the identification was performed based on the sequencing of regions ITS1/2 of ribosomal DNA (rDNA).…”
Section: Control Of Plant Pathogens and Weeds Of Embrapa (Brazilian Amentioning
confidence: 99%
“…These steps are essential because they reveal the mode(s) of action of the antagonists. In addition, a key point in the development of new biopesticides is the discovery of fungal strains with greater activity and more adapted to the agro pathosystems in which these products will be used (Marques et al, 2016;Carvalho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Screening of the antagonist potential of Trichoderma isolates has been demonstrated in scientific works for several plant pathogenic fungi, such as Macrophomina phaseolina (El-Benawy et al, 2020, Choudhary et al, 2021, Martínez-Salgado et al, 2021, Paul et al, 2021; Fusarium spp. (Pellan et al, 2020;Kumar et al, 2021;Yassin et al, 2021); Sclerotium rolfsii (Kotasthane et al, 2014;Kamel et al, 2020;Blanco et al, 2021) and Sclerotinia sclerotiorum (Marques et al, 2016;Amaral et al, 2018;Sumida et al, 2018;Carvalho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%